Novel highly selective inhibitors of ubiquitin specific protease 30 (USP30) accelerate mitophagy. Issue 15 (15th August 2018) - Kluge, Arthur F.; Lagu, Bharat R.; Maiti, Pranab; Jaleel, Mahaboobi; Webb, Michael; Malhotra, Jyoti; Mallat, Ashley; Srinivas, P. Akhila; Thompson, James E.
Graphical abstract: Highlights: Selective USP30 inhibitors. Increase protein ubiquitination. Accelerates mitophagy. Abstract: Mitophagy is one of the processes that cells use to maintain overall health. An E3 ligase, parkin, ubiquitinates mitochondrial proteins prior to their degradation by autophagasomes. USP30 is an enzyme that de-ubiquitinates mitochondrial proteins; therefore, inhibiting this enzyme could foster mitophagy. Herein, we disclose the structure–activity relationships (SAR) within a novel series of highly selective USP30 inhibitors. Two structurally similar compounds, MF-094 (a potent and selective USP30 inhibitor) and MF-095 (a significantly less potent USP30 inhibitor), serve as useful controls for biological evaluation. We show that MF-094 increases protein ubiquitination and accelerates mitophagy.